O INTEGRALISMO NA IMPRENSA DA BAHIA: O CASO DE "O IMPARCIAL" (Revista de História Regional, 2007)
The aim of this article is to analyze the relationshipbetween the Brazilian Integralist Action (Ação IntegralistaBrasileira) and the press in Bahia, more precisely with thenewspaper O Imparcial. This relationship reflected thepolitical-ideological context of the decades of 1930 and 1940,which were marked by the rising of fascism, anticommunismand the anti-fascist fight. We tried to understandthe position of the newspaper O Imparcial in face of the integralism in two different moments: the first phase,characterized by the adhesion to it, when the newspaperbecame the main way of spreading the integralistpropaganda in Bahia in the 1930s, and the second phase,defined by the separation between the newspaper and thepolitical movement, when it led a violent anti-integralist campaign in the first half of the 1940s; and we also analyzethe political interests which oriented the editorial line ofthat newspaper in both phases .